Cognitive-Behavioral Treatment of Perfectionism - Egan, Sarah; Wade, T.; Shafran, R.; Anthony, M. (Guilford Press, 2014)
This practical resource provides an evidence-based framework for treating clients struggling withperfectionism, whether as the main presenting problem or in conjunction with depression, eatingdisorders, anxiety disorders, or obsessive–compulsive disorder. Using a case formulationapproach, the authors draw on their extensive cognitive-behavioral therapy (CBT) experience topresent specific techniques and interventions. Coverage spans treatment planning, the therapeuticalliance, key obstacles that may arise, relapse prevention, and emerging research. Reproducibleassessment scales and 36 patient handouts are included; purchasers get access to a Web pagewhere they can download and print the reproducible materials in a convenient 8 1/2" x 11" size.